Mechanobiology of Epithelia From the Perspective of Extracellular Matrix Heterogeneity - Kozyrina, Aleksandra N.; Piskova, Teodora; Di Russo, Jacopo (Frontiers in Bioengineering and Biotechnology, 2020)
Understanding the complexity of the extracellular matrix (ECM) and its variability is a necessary step on the way to engineering functional (bio)materials that serve their respective purposes while relying on cell adhesion. Upon adhesion, cells receive messages which contain both biochemical and mechanical information. The main focus on mechanobiology lies in investigating the role of this mechanical coordination in regulating cellular behaviour. In recent years, this focus has additionally shifted towards cell collectives and the understanding of their behaviour as a whole mechanical continuum. Collective cell phenomena very much apply to epithelia which are either simple cell-sheets or more complex three-dimensional structures. Researchers have been mostly used the organization of monolayers to observe their collective behaviour in well-defined experimental setups in vitro. Nevertheless, recent studies have also reported the impact of ECM remodelling on epithelial morphogenesis in vivo. These new concepts, combined with the knowledge of ECM biochemical complexity are of key importance for engineering new interactive materials to support both epithelial remodelling and homeostasis. In this review, we summarize the structure and heterogeneity of the ECM before discussing its impact on the epithelial mechanobiology.